Procedural autonomy across Europe / edited by Bart Krans, Anna Nylund. - Krans, Herman Berend; Nylund, Anna (Intersentia, 2020)
This book investigates the concept of procedural autonomy of Member States in the light of EU law. Does procedural autonomy still adequately describe the powers of national lawmakers and courts to design their civil procedural systems or is it misleading? For the last few decades, Europe has been in a period of increasing Europeanisation of civil procedure. Increased powers of the EU have resulted in hard law, case law and soft law that regulate many types of domestic and cross-border civil cases. These rules have both direct and indirect implications for national procedural law. Gaining insights from selected European jurisdictions (Belgium, England and Wales, Finland, Germany, The Netherlands, Norway, Poland, Slovenia, Spain, and Sweden), this book explores the concept of procedural autonomy from different angles: Is procedural autonomy an adequate term? How is procedural autonomy understood nationally, and is there variation among the Member States? Do some types of EU law or specific characteristics of EU civil procedural law restrain procedural autonomy more than other? How can these differences be explained and is it possible to identify the sources causing such discrepancies? Procedural Autonomy across Europe is a stimulating discussion for lawyers with an interest in civil procedure.